MOBILE TRAINING MODEL BASED ON SELF - ACCESS LEARNING TO ENHANCE COMPETENCY OF DIGITAL TECHNOLOGY FOR GOVERNMENT STAFF AND GOVERNMENT PERSONNEL - Yoosamran, Jeeratchaya; Diteeyont, Watsatree (Academic Journal of Thailand National Sports University, 2023)
The objective of this research was to develop a self - directed learning-based training model for government staff and government personnel. The study was Research and Development: R&D. The target group for providing information for research is various experts related to the training of government personnel, totally 6 people and also this research was related to digital literacy, learning - based mobile training and self - access in order to explore components of the systems and develop them into suitable mobile training model for using to train government staffs. The researchers found that a suitable mobile training with the concept of self-learning to enhance digital technology performance for government staff contained several factors divided into three important parts. The first part was called “input” part which contained factors related to the self - learning approach, content analysis, training design process, and tools. The second part was called “process” which included the pre - training stage, training process, and post - training stage. The last part was called “productivity” which included learning outcomes and their attitudes toward mobile training.